Kleptoparasitic relationships between common eiders (Somateria mollissima) and large gulls in Solheimsviken, Bergen - Thorsen, Stian Dreyer (The University of Bergen, 2021)
Kleptoparasitism is defined as the theft of procured resources from another individual and is common in many species, especially so in birds. This kind of interaction is well documented between common eiders and gulls. This study is documenting the kleptoparasitic relationship between eiders and gulls in the urban inlet, Solheimsviken. The aims of the study were 1) to examine the number of gulls present in different sized groups of eiders, and whether the gull presence changed over time. 2) To examine the ratio of attacks and successful attacks from gulls in eider groups of increasing sizes. 3) To document the abundance of eiders visiting Solheimsviken. 4) To record what the eiders brought to the surface, and what the gulls managed to steal. A positive correlation between the eider group size and the number of gulls present was found. The presence of gulls in groups of eiders did change over time, with less gulls present in the groups of eiders as the season progressed. The number of attempted attacks and successful attacks did increase with increasing size of eider groups. However, the success ratio did decrease as the size of the eider groups increased. The eiders were observed bringing starfish, sea urchins, and blue mussels to the surface. There was a large bias towards starfish being the prey stolen with over half of all starfish recorded at the surface being stolen. In contrast, blue mussels recorded at the surface were only stolen approximately 10% of the times. These findings are in concordance with other studies which have shown that gulls do prefer starfish as they require more handling time at the surface by the eiders, and starfish are more energetically favorable than blue mussels. The correlation between the number of eiders and number of gulls have previously been studied with different outcomes. Some studies have shown that gulls defend their groups of eiders against other gulls, while other studies found a positive correlation in accordance with ideal free distribution. This study found a linear ...